Covid-19 and the environment - the role of the Public Health Institute - Ulm, Lea (Array, 2020)
The Croatian National Health Care Act defines the areas of activities of the public health institute, including the activities of the epidemiology of infectious diseases and chronic non-communicable diseases, public health, health promotion, environmental health, microbiology, school and adolescent medicine, mental health and addiction prevention at Zagreb City level. This paper reviews the highly variable activities in the Andrija Štampar Teaching Institute of Public Health with the aim of promoting a comprehensive approach to the COVID-19 pandemic. Human and analytical resources in the Institute, activities and rapid implementation of innovations testify to the high capacities for adaptation to emerging risks. In the Institute, it is possible to carry out a whole range of tests and to monitor the environmental factors with predominant impact on human health and safety of the Zagreb environment. The supply of safe water for human consumption in the Republic of Croatia during the current COVID-19 crisis has been uninterrupted and in accordance with applicable legislation. Also, our laboratories have been developing and introducing a method for wastewater testing for SARS-CoV-2 presence. The sludge from wastewater treatment plants is used in agriculture, and potential risks associated with the COVID-19 outbreak should be assessed prior to each application on the soil. Increased use of disinfectants during the epidemic may present a higher risk to the aquatic environment. Air quality monitoring indicates a positive impact on air quality as result of isolation measures.